11
$\begingroup$

I was trying to derive the property $$\arctan{x}+\arctan{y}=\arctan{\frac{x+y}{1-xy}}$$ for $x,y>0$ and $xy<1$ from the integral representation $$ \arctan{x}=\int_0^x\frac{dt}{1+t^2}\,. $$ I am aware of "more trigonometric" proofs, for instance using that $\tan{(\alpha+\beta)}=\frac{\tan\alpha+\tan\beta}{1-\tan\alpha\tan\beta}$, but I was willing to see if there is a proof that uses more directly the properties of the integral representation. For instance, if $x>0$, one immediately gets $$\begin{aligned} \arctan{x}+\arctan\frac{1}{x} &=\int_0^x\frac{dt}{1+t^2} + \int_0^{\frac{1}{x}}\frac{dt}{1+t^2}\\ &= \int_0^x\frac{dt}{1+t^2}+\int_x^\infty\frac{dt}{1+t^2}\\ &=\int_0^\infty \frac{dt}{1+t^2} = \frac{\pi}{2} \end{aligned}$$ sending $t\to\frac{1}{t}$ in the second integral. Similarly I tried considering $$ \int_0^x\frac{dt}{1+t^2} + \int_0^y\frac{dt}{1+t^2}=(x+y)\int_0^1\frac{1+xyt^2}{1+(x^2+y^2)t^2+x^2y^2t^4}\ dt $$ after rescaling $t\to xt$ and $t\to yt$. On the other hand, via a similar rescaling $t\to \frac{x+y}{1-xy}t$, we have $$ \int_0^\frac{x+y}{1-xy}\frac{dt}{1+t^2} = (x+y)\int_0^1\frac{1-xy}{(1-xy)^2+(x+y)^2t^2}\ dt\,. $$ By a clever choice of variable it should (must?) be possible to see that these integrals are actually the same, but I can't figure it out...

$\endgroup$
  • 1
    $\begingroup$ This identity holds for $xy<1$. In the other cases, you need to add or subtract a multiple of $\pi$ to the RHS. $\endgroup$ – bjorn93 Mar 19 at 23:28
  • $\begingroup$ True, probably I should add that in the statement of the problem, thanks $\endgroup$ – Brightsun Mar 20 at 7:33
3
$\begingroup$

We want show that \begin{eqnarray*} \int_x^{ \frac{x+y}{1-xy}} \frac{dt}{1+t^2} = \int_{0}^{y} \frac{du}{1+u^2} \end{eqnarray*} that's to say the LHS is actually independent of $x$.

The substitution \begin{eqnarray*} t=x+ \frac{u(1+x^2)}{1-ux} \end{eqnarray*} will do the trick.

The limits are easily checked and we have \begin{eqnarray*} dt= \frac{1+x^2}{(1-ux)^2} du. \end{eqnarray*} The rest is a little bit of algebra.

Note the similarity with $ \ln(a)+\ln(b) = \ln(ab)$ \begin{eqnarray*} \int_{1}^{a} \frac{dt}{t} +\int_{1}^{b} \frac{dt}{t} = \int_{1}^{ab} \frac{dt}{t}. \end{eqnarray*} And $ u=at $ \begin{eqnarray*} \int_{1}^{b} \frac{dt}{t} = \int_{a}^{ab} \frac{du}{u}. \end{eqnarray*}

$\endgroup$
  • 1
    $\begingroup$ Nice, thank you. I think the substitution is slightly more insightful written as $t=\frac{x+u}{1-ux}$ due to the similarity with $\frac{x+y}{1-xy}$. Just a curiosity, did you arrive at the result by trial and error or did you have some guiding principle? $\endgroup$ – Brightsun Mar 19 at 22:14
  • 1
    $\begingroup$ Don't tell anyone ... but the first guess written in my notebook is \begin{eqnarray*} t=x + \frac{y(1+u^2)}{1-uy}. \end{eqnarray*} "Trial and error" or "guiding principle"? A bit of both. Thanks, this is a cool problem. $\endgroup$ – Donald Splutterwit Mar 19 at 22:21
0
$\begingroup$

hint

If we put

$$t=\frac{x+y}{1-xy}u$$

the left integral becomes

$$\int_0^1\frac{1}{1+(\frac{x+y}{1-xy})^2u^2}\frac{x+y}{1-xy}du$$

$\endgroup$
  • $\begingroup$ I think that's what I did in the last step of my question..? $\endgroup$ – Brightsun Mar 19 at 20:59
  • $\begingroup$ Sorry, i was thinking about corona, i did not read your question as i had to do. the problem is that i cannot delete from mobile. i hope no one will downvote. $\endgroup$ – hamam_Abdallah Mar 19 at 21:04
0
$\begingroup$

Fixing $y$, define $f(x):=\arctan x+\arctan y-\arctan\frac{x+y}{1-xy}$ so $f(0)=0$ and$$\begin{align}f^\prime(x)&=\frac{1}{1+x^2}-\frac{1}{1+\left(\frac{x+y}{1-xy}\right)^2}\partial_x\frac{x+y}{1-xy}\\&=\frac{1}{1+x^2}-\frac{(1-xy)^2}{(1+x^2)(1+y^2)}\frac{1-xy-(x+y)(-y)}{(1-xy)^2}\\&=\frac{1}{1+x^2}-\frac{(1-xy)^2}{(1+x^2)(1+y^2)}\frac{1+y^2}{(1-xy)^2}\\&=0,\end{align}$$i.e. $f(x)=0$ for all $x$.

$\endgroup$
0
$\begingroup$

Another change of variables that works, very similar to that in the answer by @DonaldSplutterwit, is the following: $$ t=f(u)=\frac{1-u\sigma}{u+\sigma}\,,\qquad\text{with}\ \ \sigma(x,y)=\frac{1-xy}{x+y}\,. $$ It is more symmetric, since it works both for $$ \int_x^{1/\sigma}\frac{dt}{1+t^2}=\int_0^y\frac{du}{1+u^2} $$ and for $$ \int_y^{1/\sigma}\frac{dt}{1+t^2}=\int_0^x\frac{du}{1+u^2}\,. $$ Indeed, $$ f(0)=\frac{1}{\sigma}\,,\qquad f(x)=y\,,\qquad f(y)=x $$ and $$ dt=-\frac{1+\sigma^2}{(u+\sigma)^2}du\,,\qquad \frac{1}{1+t^2}=\frac{(u+\sigma)^2}{(1+\sigma^2)(1+u^2)}\,. $$ It also has the property of reducing to the inversion as $xy\to1^-$, namely $\sigma\to0^+$, since $$ f(u)\big|_{\sigma=0}=\frac{1}{u}\,, $$ and we get back $$ \int_{x}^\infty \frac{dt}{1+t^2} = \int_{0}^{\frac{1}{x}}\frac{du}{1+u^2}\,. $$ In fact, $f$ is also an involution $f(f(u))=u$ and also allows to run the proof "forward" in the following way $$ \int_0^x\frac{dt}{1+t^2}+\int_0^y\frac{dt}{1+t^2}=\int_0^x\frac{dt}{1+t^2}+\int_x^{\frac{1}{\sigma}}\frac{du}{1+u^2}=\int_0^{\frac{1}{\sigma}}\frac{dt}{1+t^2}\,, $$ where we let $t=f(u)$ in the second integral.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.